A guide to advanced linear algebra - Weintraub, Steven H. (Dolciani mathematical expositions, 2011)
"This book provides a rigorous and thorough development of linear algebra at an advanced level, and is directed at graduate students and professional mathematicians. It approaches linear algebra from an algebraic point of view, but its selection of topics is governed not only for their importance in linear algebra itself, but also for their applications throughout mathematics"--